Abnormalities in Glucose Metabolism, Appetite-Related Peptide Release, and Pro-inflammatory Cytokines Play a Central Role in Appetite Disorders in Peritoneal Dialysis - Avila-Carrasco, Lorena; Pavone, Mario A.; González, Elena; Aguilera-Baca, Álvaro; Selgas, Rafael; del Peso, Gloria; Cigarran, Secundino; López-Cabrera, Manuel; Aguilera, Abelardo (Frontiers in Physiology, 2019)
Abstract Background. Appetite disorders are frequent and scantly studied in peritoneal dialysis (PD) patients and are associated with malnutrition and cardiovascular complications. Objetive: We investigated the relationship between uremic insulin resistance, pro-inflammatory cytokines and appetite-related peptides release (ARPr) with eating-behaviour disorders in PD patients. Methods. We included 42 PD patients (12 suffering anorexia, 12 obese with high food-intake and 18 asymptomatic) and 10 controls. We measured blood levels of ARPr including orexigens (neuropeptide-Y [NPY], ghrelin and nitric-oxide), anorexigens (cholecystokinin, insulin, corticotropin-releasing factor, leptin and adiponectin [Ad]), and cytokines (TNF-, sTNF-R2 and IL-6) both at baseline and after administering a standard-food stimulus (SFS). We also measured the expression of TNF-, leptin and Ad-encoding mRNAs in abdominal adipose tissue. We compared these markers with eating motivation measured by a visual analogue scale (VAS). Results. Anorexics showed both little appetite, measured by a VAS, and low levels of orexigens that remained constant after SFS, coupled with high levels of anorexigens at baseline and after SFS. Obeses showed higher appetite, increased baseline levels of orexigens, lower baseline levels of anorexigens and cytokines and two peaks of NPY after SFS. The different patterns of ARPr and cytokines pointed to a close relationship with uremic insulin resistance. In fact, the euglycemic-hyperglycemic clamp reproduced these disorders. In anorexics, TNF- fat expression was increased. In obese patients, leptin expression in fat tissue was down-regulated and showed correlation with the appetite. Conclusion. In PD, appetite is governed by substances that are altered at baseline and abnormally released. Such modulators are controlled by insulin metabolism and cytokines and, while anorexics display inflammatory predominance, obese patients predominantly display insulin resistance.